PENGARUH PERSONALITAS AUDITOR DAN ETIKA PROFESI TERHADAP PENERIMAAN PERILAKU AUDIT DISFUNGSIONAL (Studi Empiris BPK RI Perwakilan Provinsi Riau) - Wulan Oktaviani; Hardi '; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose that wish to be reached in this research is to test empirically and analyze variable auditor personality and professional ethics which directly influence the acceptance of dysfunctional audit behavior. Data in this research were obtained from questionnaires (primary). Population in this research is eksternal auditors of goverment at BPK Riau Province. Data analysis conducted with multiple linear regression model with help of software SPSS version 20.0. Result of this research show that variable auditor personality has significant effect to ecceptance of dysfunctional audit behavior. It comes from the probability significance that is 0.000. Professional ethics has a significant effect to ecceptance of dysfunctional audit behavior. It comes from the probability significance that is 0.002. The result of F test has a significant value that is 0.000. The conclusion can be made from the result that there is an effect of auditor personality and professional ethics together to ecceptance of dysfunctional audit behavior.Keywords : auditor personality, professional ethics, dysfunctional audit behavior